1993
DOI: 10.2165/00007256-199315020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Commercially Marketed Supplements for Bodybuilding Athletes

Abstract: We conducted a survey of 624 commercially available supplements targeted towards bodybuilding athletes. Over 800 performance claims were made for these supplements. Supplements include amino acids, boron, carnitine, choline, chromium, dibencozide, ferulic acid, gamma oryzanol, medium chain triglycerides, weight gain powders, Smilax compounds and yohimbine. Many performance claims advertised were not supported by published research studies. In some instances, we found no research to validate the claims; in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 83 publications
0
22
0
3
Order By: Relevance
“…Having been consumed by indigenous Peruvians for centuries [2], the rumoured energy enhancing properties of the root of the maca plant have recently gained notoriety [5], and as such products such as ME have grown in popularity amongst athletes. Previous research exploring the scientific efficacy of maca supplementation on exercise performance has shown that consumption of maca improves various markers associated with sports performance [8]; however the trial was not placebo controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having been consumed by indigenous Peruvians for centuries [2], the rumoured energy enhancing properties of the root of the maca plant have recently gained notoriety [5], and as such products such as ME have grown in popularity amongst athletes. Previous research exploring the scientific efficacy of maca supplementation on exercise performance has shown that consumption of maca improves various markers associated with sports performance [8]; however the trial was not placebo controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Maca derivatives are gaining popularity as dietary supplements consumed either to enhance sexual desire or athletic performance [4] [5]. However little data is available to describe whether or not these postulated effects are of scientific merit.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, g-oryzanol is widely employed as an anabolic agent by bodybuilding athletes (Rosenbloom et al, 1992;Grunewald and Bailey, 1993). In fact, g-oryzanol is consumed in the belief that it may elicit anabolic effects ranging from increased testosterone production and release to stimulating human growth hormone release.…”
Section: Studies In Other Disordersmentioning
confidence: 99%
“…Smilax supplements are often produced from Smilax medica, Smilax officinalis and Smilax regelii belowground parts via extraction, and are rich in a category of plant sterols called saponins including sarsasapogenin (sarsapogenin), smilagenin (a derivative of sapogenin), sitosterol and stigmasterol. Bodybuilders consume Smilax supplements for their purported anabolic effects,11 mistakenly perceiving sarsaparilla sterols as prohormonal compounds that can be converted into testosterone by the human body and subsequently increase muscle mass, power, maximal performance and overall metabolism, though these possibilities have been disproved 12 13. Other benefits attributed to Smilax supplements include increasing endurance or energy, promoting recovery, lowering body fat12 and enhancing immune function 13.…”
Section: Smilax (Sarsaparilla)mentioning
confidence: 99%